2023
DOI: 10.3389/frsle.2023.1087196
|View full text |Cite
|
Sign up to set email alerts
|

The role of neuromuscular function in sleep apnea pathogenesis and management: A consensus of experts

Abstract: Study objectivesAlthough the importance of upper airway assessment in the consideration of obstructive sleep apnea (OSA) is recognized, there are current limitations in our approach to assessment.MethodsWe convened a group of experts in upper airway neuromuscular physiology and anatomy, sleep apnea endophenotypes, novel therapeutics and sleep epidemiology to summarize existing literature and delineate future opportunities to utilize and incorporate innovative and less invasive techniques focused on upper airwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Some of these issues related to the diagnostic paradigm of OSA are being discussed by academic experts (Mehra et al, 2023) and have been recently considered while designing larger industry-sponsored trials testing the effects of pharmacotherapies on OSA severity (Clinicaltrials.gov, 2022a,c;Hedner et al, 2022). The Mariposa trial was a large 25-center phase 2b trial recently concluded, which tested the effect of AD109 over a month of therapy in patients with a baseline AHI4 between 10 and 45 events/h.…”
Section: Interpretation Challenges Of the Proof-of-concept Trialsmentioning
confidence: 99%
“…Some of these issues related to the diagnostic paradigm of OSA are being discussed by academic experts (Mehra et al, 2023) and have been recently considered while designing larger industry-sponsored trials testing the effects of pharmacotherapies on OSA severity (Clinicaltrials.gov, 2022a,c;Hedner et al, 2022). The Mariposa trial was a large 25-center phase 2b trial recently concluded, which tested the effect of AD109 over a month of therapy in patients with a baseline AHI4 between 10 and 45 events/h.…”
Section: Interpretation Challenges Of the Proof-of-concept Trialsmentioning
confidence: 99%